All-cause mortality and risk factors in a cohort of retired military male veterans, Xi'an, China: an 18-year follow up study - Li Liang S; Zhang Lei; Shi Qiu L; Huang Jiu Y; Wang Bo; Men Ke; He Yao; Sai Xiao Y; Choi Bernard CK; Yan Yong P (BMC, 2007)
Abstract Background Risk factors of all-cause mortality have not been reported in Chinese retired military veterans. The objective of the study was to examine the risk factors and proportional mortality in a Chinese retired military male cohort. Methods A total of 1268 retired military men aged 55 or older were examined physically and interviewed using a standard questionnaire in 1987. The cohort was followed up every two years and the study censored date was June30, 2005 with a follow-up of up to 18 years. Death certificates were obtained from hospitals and verified by two senior doctors. Data were entered (double entry) by Foxbase, and analysis was carried out by SAS for Windows 8.2. Multivariate Cox proportional hazard regression model was used to compute hazard ratio (HR) and 95% confidence interval (CI). Results The total person-years of follow-up was 18766.28. Of the initial cohort of 1268 men, 491 had died, 748 were alive and 29 were lost to follow up. Adjusted mortality (adjusted for age, blood pressure, body mass index, cholesterol, triglycerides, alcohol, exercise, and existing disease) was 2,616 per 100,000 person years. The proportional mortality of cancer, vascular disease and Chronic Obstructive Pulmonary Disease (COPD) were 39.71%, 28.10% and 16.90% respectively. Multivariate analysis showed that age, cigarettes per day, systolic blood pressure, triglyceride, family history of diseases (hypertension, stroke and cancer), existing diseases (stroke, diabetes and cancer), body mass index, and age of starting smoking were associated with all-cause mortality, HR (95%CI) was1.083(1.062-1.104), 1.026(1.013-1.039), 1.009(1.003-1.015), 1.002(1.001-1.003), 1.330(1.005-1.759), 1.330(1.005-1.759), 1.444(1.103-1.890), 2.237(1.244-4.022), 1.462(1.042-2.051), 2.079(1.051-4.115), 0.963(0.931-0.996)and 0.988(0.978-0.999)respectively. Compared with never-smokers, current smokers had increased risks of total mortality [HR 1.369(1.083-1.731)], CHD [HR 1.805 (1.022-3.188)], and lung cancer [HR 2.939 (1.311-6.585)]. Conclusion The three leading causes of diseases were cancer, CHD and stroke, and COPD. Aging, cigarette smoking, high systolic blood pressure, high triglyceride, family history of cancer, hypertension and stroke, existing cases recovering from stroke, diabetes and cancer, underweight, younger age of smoking were risk factors for all-cause mortality. Quitting cigarette smoking, maintaining normal blood pressure, triglyceride and weight are effect control strategies to prevent premature mortality in this military cohort.